Strategi Pemberdayaan UMKM Melalui Pelatihan Pembuatan Iklan Digital untuk Optimalisasi Pemasaran Komoditas Lokal di Kecamatan Kayen - Eko Prasetyo; Adhi Priyanto; Sthepanus Widjaja (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Entrepreneurs are individuals or groups engaged in business activities to produce goods or services. To increase product visibility, they need to implement marketing strategies, including the use of digital media. However, many UMKM actors in Kayen District, Pati Regency, still rely on manual marketing methods or word-of-mouth promotion. To address this issue, Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) of STMIK AKI Pati organized a digital marketing training program for local UMKM. The goal is to enhance their ability to market their products or services effectively through digital platforms. The training is conducted in three stages: first, introducing the basic concepts of digital marketing; second, teaching participants how to use graphic design software such as Canva and Photoshop to create logos and promotional flyers; and third, guiding them on how to register and use e-commerce platforms like Shopee and Tokopedia, as well as how to advertise effectively on social media. This program aims to help UMKM actors in Kayen understand the importance of digital marketing and develop more effective strategies to promote and sell their products online.